Ion beam modification of the Ni-Si solid-phase reaction: The influence of substrate damage and nitrogen impurities introduced by ion implantation. (13th October 2020) - van Stiphout, K; Geenen, F A; Santos, N M; Miranda, S M C; Joly, V; Demeulemeester, J; Mocuta, C; Comrie, C M; Detavernier, C; Pereira, L M C; Temst, K; Vantomme, A
Abstract: We report on the growth of thin NiSi films via the thermal reaction of Ni layers (13–35 nm) with Si(100) substrates modified by ion implantation. By introducing substrate damage or nitrogen impurities prior to the solid-phase reaction, several properties of the NiSi films can be modified: the formation temperature, texture, diffusion-limited growth rate and morphological stability. As some of the modifications to the NiSi films are rooted in the early silicide phases preceding the NiSi phase, particularly its formation temperature, special attention is devoted to the growth of the amorphous Ni-Si alloy and the crystalline δ -Ni2 Si and θ -Ni2 Si phases. We employed a number of experimental techniques, including in situ synchrotron x-ray diffraction (XRD), in situ Rutherford backscattering spectrometry (RBS), in situ sheet resistance measurements, ex situ ion beam channelling and ex situ pole figure measurements. We show that both the formation temperature of the NiSi films and the intensity of epitaxial and axiotaxial components of the NiSi texture can be either lowered or raised by selecting appropriate implantation conditions. Agglomeration of the NiSi films at high temperature (> 700 °C) can be slowed down, either by slowing down the mobility of the Ni and Si atoms, or by removing the morphologically destabilizing axiotaxial texture. Our results emphasize the strong interwoven nature of phase formation, texture and morphological degradation. We illustrate that the kinetics of the early stages of thin film reactions consist of more than just diffusion, i.e. nucleation can also play a crucial role.